Experimental Study of Compressive Strength and Tensile Strength of Foam Mortar with the Addition of Polyethylene Fibers - Marpen, Rio; Amiruddin, Amiruddin; Rahmadona, Efrilia; Islamiati, Indah; Labais, Yusni Septiani (CIVED, 2024)
Mortar is a building material of sand, cement, and water that is stirred until homogeneous. So that a light mortar can be obtained, this can be done by mixing the mortar with a foaming agent. Adding polyethylene fiber increases the compressive strength, tensile strength, modulus of elasticity, and brittleness of lightweight mortar. The percentage of added fiber is 0%, 0.25%, 0.5%, 0.75% and 1%. The average density of lightweight mortar added with polyethylene fiber is 895.316 kg/m3. The optimal compressive strength with a fiber ratio of 0.5% polyethylene fiber is 3461.429 kPa, an increase of 172.906% compared to 0% polyethylene fiber. The optimal tensile strength of 0.5% polyethylene fiber is 1218.384 kPa, an increase of 364.917% compared to 0% polyethylene fiber. Based on the results of foam mortar experiments using a foam agent with polyethylene fiber, this is classified as type O mortar, not recommended for interior and exterior walls that do not support structural loads.